Conceptual Framework for Cross-Disciplinary Approaches to Climate-Resilient Infrastructure Development - Ayomide Kashim Ibrahim; Adaobu Amini-Philips; Wasiu Eyinade (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Climate change poses unprecedented challenges to infrastructure systems worldwide, increasing vulnerability to extreme weather events, sea level rise, and resource stress. Addressing these risks requires not only innovative engineering but also holistic, cross-disciplinary approaches that integrate technical, environmental, socio-economic, and governance perspectives. This proposes a conceptual framework for cross-disciplinary approaches to climate-resilient infrastructure development, emphasizing the integration of diverse fields including civil engineering, environmental science, urban planning, economics, and social sciences. The framework is grounded in resilience theory, systems thinking, and collaborative governance, enabling a comprehensive understanding of infrastructure as part of an interconnected socio-ecological-technical system. The model identifies five core dimensions: technical, environmental, socio-economic, policy and governance, and knowledge and data. The technical dimension addresses climate-responsive design, material innovation, and adaptive engineering practices. The environmental dimension highlights ecosystem-based strategies and nature-based solutions that complement gray infrastructure. Socio-economic considerations ensure that resilience measures are equitable, cost-effective, and inclusive, accounting for community needs and long-term value. Policy and governance structures provide the regulatory backbone, aligning national adaptation strategies with global agreements such as the Paris Accord and the Sustainable Development Goals. Finally, the knowledge and data dimension emphasizes the role of digital twins, climate models, and knowledge-sharing platforms in supporting evidence-based decision-making. The proposed framework underscores the dynamic interactions between these dimensions, facilitated by feedback loops, participatory mechanisms, and adaptive management strategies. By bridging disciplinary silos, it offers a pathway for designing, implementing, and governing infrastructure that is both climate-resilient and socially responsive. Future directions include leveraging artificial intelligence for predictive climate risk assessment, blockchain for transparency in resilience financing, and global best-practice adoption to harmonize standards. This framework contributes to advancing integrated, future-oriented approaches for sustainable infrastructure development in the face of climate uncertainty.